2014
DOI: 10.1186/s13068-014-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic analysis of lignocellulolytic microbial communities involved in high-solids decomposition of rice straw

Abstract: BackgroundNew lignocellulolytic enzymes are needed that maintain optimal activity under the harsh conditions present during industrial enzymatic deconstruction of biomass, including high temperatures, the absence of free water, and the presence of inhibitors from the biomass. Enriching lignocellulolytic microbial communities under these conditions provides a source of microorganisms that may yield robust lignocellulolytic enzymes tolerant to the extreme conditions needed to improve the throughput and efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
(50 reference statements)
4
24
0
2
Order By: Relevance
“…Simultaneously, although the gene abundance of GH3E was higher than the gene abundance of GH1B from the overall composting process, in the thermophilic phase of composting, the abundance of fungi gene decreased significantly such as GH3E-6-9 and GH3E-6-14 (Fig 6c), while the abundance of bacterial gene showed D r a f t increasing trends such as GH1-3-8, GH1-2-5, GH1-3-20, GH1-4-24, GH3B-3-16 and GH3B-2-12 (Fig 6a, b). A similar phenomenon was found by Simmons et al (2014) where it was shown that several GH family 1 proteins (i.e., bacterial genes) were significantly overexpressed in the thermophilic community, whereas GH family 3 (predominantly fungal) genes were significantly overexpressed in the mesophilic community. Therefore, we found in our experiment that the GH1 and GH3 family bacteria community play a more important role than the GH3 family fungi community in producting β-glucosidase and degradation cellulose at the later thermophilic stage of composting.…”
Section: R a F Tsupporting
confidence: 82%
“…Simultaneously, although the gene abundance of GH3E was higher than the gene abundance of GH1B from the overall composting process, in the thermophilic phase of composting, the abundance of fungi gene decreased significantly such as GH3E-6-9 and GH3E-6-14 (Fig 6c), while the abundance of bacterial gene showed D r a f t increasing trends such as GH1-3-8, GH1-2-5, GH1-3-20, GH1-4-24, GH3B-3-16 and GH3B-2-12 (Fig 6a, b). A similar phenomenon was found by Simmons et al (2014) where it was shown that several GH family 1 proteins (i.e., bacterial genes) were significantly overexpressed in the thermophilic community, whereas GH family 3 (predominantly fungal) genes were significantly overexpressed in the mesophilic community. Therefore, we found in our experiment that the GH1 and GH3 family bacteria community play a more important role than the GH3 family fungi community in producting β-glucosidase and degradation cellulose at the later thermophilic stage of composting.…”
Section: R a F Tsupporting
confidence: 82%
“…Except for D99, members from the orders Bacillales, Clostridiales, Actinomycetales, and Thermoanaerobacterales abound throughout the composting process, and most CDSs related to plant biomass degradation were classified as belonging to members of these orders. Actinomycetales are commonly found in compost, particularly in the thermophilic and mature stages11162554, and also in thermophilic microbial consortia enriched from compost3055. Indeed, in our data the relative abundance of CDSs assigned to this order involved with lignocellulosic biomass degradation is largest at D30 and D78 (34.4% and 49%, respectively).…”
Section: Resultsmentioning
confidence: 49%
“…Previous studies on employing microbial consortia for lignocellulose breakdown utilized both complex373839 and defined media404142.…”
Section: Discussionmentioning
confidence: 99%